ANALISIS IMPLEMENTASI MBKM-KKNT DI SMK DHARMAWANITA KECAMATAN KROMENGAN KABUPATEN MALANG - Rini Agustina; Hari Lugis Purwanto; Syahminan; Yoyok Seby Dwanoko; Wiji Setiyaningsih; Gaguk Susanto; Kurriawan Budi pranata (Department of System Information, 2023)
This study aims to determine the results of the evaluation analysis of the MBKM Program which includes the role of students, the role of lecturers and the role of partners in the success of the MBKM-KKNT program. The type of research used is quantitative. Data collection techniques used are interviews, and questionnaires. The data was obtained from an independent team that directly recorded the suitability of the roles of students, lecturers and partners. The data was processed using multiple linear regression analysis and correlation. Respondents in this study were students, lecturers and partners with a total of 46 people. The results of this study: (1) Students contributed 37%, 2) Lecturers contributed 37% and 3) Partners contributed 26%. The role of students is dominated by the aspect of students being able to communicate well with all parties and students having a high work ethic. The role of the lecturer in the implementation aspect makes a significant contribution where the Study Program's Work Instructions on MBKM can help implement MBKM activities in the field. Meanwhile, the aspect of Study Program facilities facilitates MBKM-KKNT activities well. While the role of Partners is more dominated by the MBKM-KKNT work factor which has a positive impact on the village community and Cooperation related to Thematic KKN can be continued considering that MBKM-KKNT activities are beneficial to the community.